FÍSICA PARA TODOS: UM EXPERIMENTO SOBRE GRAVIDADE - Eckhardt, Gustavo; Pereira, Ygor Duarte; Andreatta, Ricardo; Toniazzo, Nelson Adelar; Blume, Paula Bellé; Schmidt, Pedro Afonso (Salão do Conhecimento, 2019)
Projeto de extensão do projeto Física para todos